A Virtual World Construction Method Using Captured Images - Applications for Virtual Shopping - Ozaki, Nobuyuki; Takada, Kaoru (International Journal of Virtual Reality, 2001)
Procedures for interactively employing captured images for virtual world construction are described using prototypes of two applications for virtual shopping. Virtual reality technology, especially the image based rendering technique, enables us to exhibit products in a sophisticated way. With a concert ticket reservation system the customer can check the view of the stage from any seat. These images are synthesized from captured images and are not created from less realistic computer graphics. With a catalog shopping system that uses captured images to show products, the customer can observe them stereoscopically and vary the viewing angle interactively. These systems are implemented into kiosktype terminals. Purchases can be made with IC-card type electronic cash.